More Information = Less Aggression? Impact of Information Asymmetry on Chinese Patients' Aggression - Xu, Yuepei; He, Wen (Frontiers in Public Health, 2019)
Background: Information asymmetry is a widely studied economic phenomenon. It refers to the situation in which one group in a transaction has more information than the other. Nowadays, information asymmetry has been studied not only as a financial topic but also as a potential reason for essential social problems. Objective: To take Chinese doctor-patient relationship as an example and investigate the relationship among information asymmetry, trust level, and aggression behavior using an experimental design. Methods: A total of 44 undergraduates (12 males, 32 females; mean age =19.11, SD =0.84) took part in our experiment. Different slides and guidance were used to create a virtual information asymmetry situation, and we use Wake Forest physician trust scale (WFPTS) and hot sauce allocation paradigm to measure their trust level and aggression, respectively. Results: Participants in the information asymmetry group allocated significantly more hot sauce to the doctor (p<.005, d=1.09), and displayed significantly lower trust level (p<.05, d=˗0.78) than the control group. Patients’ trust level is a significant partial mediator (95% confidence interval [˗1.39, ˗0.05]). Conclusion: Asymmetric information may arouse patients’ aggression and lower their trust in doctors. Patients’ trust level is also a significant partial mediator between their aggression and information asymmetry. The current study reinforces the urgent need for information openness in the Chinese medical system.